ANALISIS KINER.IA PENJUALAN LANGSUNG PRODUK PINTU JATI (STUDI KASUS : INDUSTRI PENGOLAHAN KAYU JATI CEPU) - Caslam Caslam; Hariyatno Dwiprabowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
This study is aimed to analyzing direct selling performance of leak door processing of Perum Perhutani in Cepu.Performance of direct selling policy of the corporate can be measured by the capability in profit making, the rate of growth of total assets, control of market share, and capability 10 be survived in short or long runs.The result of Break-even Point (BEP) analysis of Cepu teak wood processing industry shows that the selling revenue of teak door product is lower than BEP, or it is only 43,49 %. It shows that direct selling policy was unfavorable for marketing strategy of leak door product. Further analysis shows that through direct selling the realization of teak door product sale was far below the selling plan, i.e. only 84. 70 % of the volume and 15.30% of the price targets, respectively.